Total Ischemic Time Versus Door-To-Balloon Time As An Outcome Predictor In St-Elevation Myocardial Infarction - Sigal, MD, Adam; Rajagopalan, MD, Priya; Fadahunsi, MD, Opeyemi; Koslow, MD, Michael; Wasser, PhD, Tom; Mengel, RN, Vanessa Cambria; Barbera, MD, Charles (Journal of Medical Biomedical and Applied Sciences, 2018)
BACKGROUNDAcute Coronary Syndrome is a common presenting condition to the emergency department and early reperfusiontherapy for patients with an ST-Elevation Myocardial Infarction (STEMI) with Percutaneous Coronary Intervention is therecommended treatment. The American Heart Association / American College of Cardiology has a 60 minutes goal forrestoration of coronary flow from the time of patient arrival.OBJECTIVETo review the impact of rapidly identifying STEMI patients and expediting transfer to the interventional cardiology suiteon restoration of blood flow times and metrics of cardiac injury, such as peak troponin and ejection fraction. To reviewthe impact of total ischemic time on similar metrics.METHODSWe conducted a single site retrospective review on STEMI patients undergoing the expedited process for reperfusioncompared to standard process.RESULTSExpedited transfer of patients to the cardiac catheterization suite resulted in significantly lower door-to-balloon times forpatients undergoing the âdrive-byâ process (mean 31.03, SD 4.05 vs mean 68.72, SD 45.09, p < 0.001), compared tousual care. The improved times, however, did not translate into improved metrics of peak troponin value or LVEF. Therewas a significantly lower peak troponin level (mean 57.14, SD 86.51 vs 97.73, SD 152.43, p=0.017) and a greater LVEFpercent at six months (56.41, SD 10.46 vs 52.56, SD 11.93, p = 0.039) for those with < 4 hour symptoms than thosewith 4 hours of symptoms.CONCLUSIONSymptom onset to balloon time has a greater impact on cardiac morbidity than door-to-balloon time.